Analisis Kemampuan Literasi Sains Peserta Didik SMA Kelas X IPA di Kota Makassar dalam Menyelesaikan Soal PISA - Zuhri, Maisarah Muaazarah; Adnan, Adnan; Saparuddin, Saparuddin (Bioscientist : Jurnal Ilmiah Biologi, 2023)
One of the skills that is important for students to have in the 21st century is scientific literacy. However, the scientific literacy scores of Indonesian students are still far below international standard scores. This study was to determine the scientific literacy skills of class X IPA high school students in Makassar City in solving PISA questions. The method used is descriptive quantitative. The population includes all students of class X IPA in Makassar City. A sample of 254 people from SMA Negeri 6 Makassar, SMA Negeri 21 Makassar, SMA Negeri 5 Makassar, SMA Negeri 9 Makassar, SMA Negeri 16 Makassar, SMA Negeri 4 Makassar, SMA Negeri 20 Makassar, and SMA Negeri 14 Makassar. The technique of determining the sample by cluster random sampling and simple random sampling. The data collection technique is in the form of multiple-choice questions of 25 numbers. The results of the data analysis showed that the percentage of students' scientific literacy skills was in the moderate category of 50% for 127 people. Furthermore, 12.2% in the high category were 31 people, 5.91% in the very high category were 15 people, 31.89% in the low category were 81 people, and 0% in the very low category were 0 people. The highest average score of scientific literacy skills from the three aspects of scientific literacy competence is found in the item evaluating and designing scientific questions, namely 33.92 in the moderate category.